The Oxford handbook of contemporary British and Irish poetry - Robinson, Peter, 1953- (Oxford : Oxford University Press, 2013)
This book offers thirty-eight chapters of ground breaking research that form a collaborative guide to the many groupings and movements, the locations and styles, as well as concerns (aesthetic, political, cultural and ethical) that have helped shape contemporary poetry in Britain and Ireland. The book's introduction offers an anthropological participant-observer approach to its variously conflicted subjects, while exploring the limits and openness of the contemporary as a shifting and never wholly knowable category. The five ensuing sections explore: a history of the period's poetic movements; its engagement with form, technique, and the other arts; its association with particular locations and places; its connection with, and difference from, poetry in other parts of the world; and its circling around such ethical issues as whether poetry can perform actions in the world, can atone, redress, or repair, and how its significance is inseparable from acts of evaluation in both poets and readers.
Includes bibliographical references and index.
Keywords: English poetry -- 21st century -- History and criticism; English poetry -- 20th century -- History and criticism; Northern Ireland -- In literature; Ireland -- In literature